2012
DOI: 10.1002/anie.201202369
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Enantiomers and CD Spectra of Au40(SCH2CH2Ph)24: Spectroscopic Evidence for Intrinsic Chirality

Abstract: Chirality unveiled: Thiolate-protected Au40(SR)24 clusters were enantioenriched using an HPLC approach. CD spectra show strong mirror-image responses, indicating the intrinsic chirality of a cluster of unknown structure protected with achiral ligands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
134
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 35 publications
6
134
1
2
Order By: Relevance
“…21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Resultsunclassified
“…21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Resultsunclassified
“…Recent studies furthermore showed even longer staples such as Au 3 (SR) 4 , 2 Au 4 (SR) 5 3 or Au 5 (SR) 6 . Particularly stable clusters were found to be Au 25 (SR) 18 , 5,6 Au 38 (SR) 24 , 7 Au 40 (SR) 24 , 8,9 Au 102 (SR) 44 , 10 and Au 144 (SR) 60 , 11 although later a large number of stable clusters has been found (see examples in ref. Particularly stable clusters were found to be Au 25 (SR) 18 , 5,6 Au 38 (SR) 24 , 7 Au 40 (SR) 24 , 8,9 Au 102 (SR) 44 , 10 and Au 144 (SR) 60 , 11 although later a large number of stable clusters has been found (see examples in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ac ouple of enantioseparation methods,i ncluding chiralcounterion-induced resolution [12] and chiral liquid chromatography [13] have been employed to obtain the nanocluster enantiomers.H owever,o wing to the shielding effect of the achiral phosphine ligands of Au 20 ,b oth methods are ineffective in separating Au 20 ( Figure S2 and S3). Currently, ac ouple of enantioseparation methods,i ncluding chiralcounterion-induced resolution [12] and chiral liquid chromatography [13] have been employed to obtain the nanocluster enantiomers.H owever,o wing to the shielding effect of the achiral phosphine ligands of Au 20 ,b oth methods are ineffective in separating Au 20 ( Figure S2 and S3).…”
mentioning
confidence: 99%